Direct Hydroxylation of Benzene to Phenol Using Palladium-Titanium Silicalite Zeolite Bifunctional Membrane Reactors - Wang, X.; Meng, B.; Tan, X.; Zhang, X.; Zhuang, S.; Liu, Lihong. (American Chemical Society, 2014)
A series of titanium silicalite zeolite catalysts were successfully incorporated inside a Pd membrane reactor aiming to improve the direct hydroxylation of benzene to phenol. The correlation between the membrane structure and the reaction efficiency was investigated. The influences of reactor configuration, feed mode, and catalysts on benzene conversion, product yield, hydrogen conversion, and water production rate were examined in detail. The reaction was very sensitive to the porosity of Ti-containing zeolite film and the bonding state of the titanium atom in the titanosilicates (i.e., framework and extraframework titanium). The framework titanium could adsorb active oxygen species to form Ti peroxo species which would suppress the decomposition, while the extraframework titanium promoted the decomposition of active oxygen species leading to more water production. Large inter- and intracrystalline pores as well as mesopores provided the reactive species greater opportunity to contact directly with framework titanium resulting in high reaction activity and hydrogen selectivity (based on the phenol production). Furthermore, these intraparticle pores helped the reactants more favorably to reach the active site than these intercrystalline pores. In contrast, the compact titanium silicalite film with smaller pore size was disadvantageous to the reaction due to the slower diffusion of the reactants and products through the zeolite layer. A possible reaction pathway of palladium–titanium silicalite zeolite (Pd–TS) composite membrane for the direct hydroxylation of benzene to phenol was also proposed based on the reaction results.